In Vitro studies of bioactive glass/polyhydroxybutyrate composites - Paiva,André Oliveira (2006)
Bioactive materials can help bone reparation and regeneration by offering support to bone growth. In vitro studies of bioactive glass/polyhydroxybutyrate composites were carried out to evaluate the influence of the composition on the bioactivity through the presence of calcium phosphate (Ca-P) on the layer formed when the substrates were immerse in simulated body fluid (SBF). The in vitro tests were carried out by soaking the composites bioactive glass/polyhydroxybutyrate 30/70 and 40/60 in SBF. The surface of the composites was analyzed by Scanning Electron Microscopy (SEM) with Energy Dispersive Spectroscopy (EDS) and also via x ray Diffraction (XRD). The solutions were analyzed by Inductively Couple Plasma (ICP). SEM images show a formation of a Ca-P rich layer on surface of composites. XRD results characterized the layer as calcium hydrogen phosphate. Ca/P ratios found via EDS results show a value close to 1.67. According to ICP results, the Ca e P ions are from SBF.